Management and outcome of severe head injuries in the Trent region 1985-90. Issue 12 (December 1992) - Elias-Jones, A C; Punt, J A; Turnbull, A E; Jaspan, T
Abstract : In a five year period, 39 children (29 boys, 10 girls) aged 2 months to 13 years (mean 7.8 years) were studied who had suffered a major head injury (29 road traffic accidents, six falls, and four non-accidental injury). The injury had been assessed clinically and by cranial computed tomography or cranial ultrasound (in a single baby of 2 months). Initial Glasgow coma scores for all subjects ranged from 3-11 (mean 5.5), intact survivors 5-11 (7.4), minor handicap 4-11 (6.1), major handicap 3-6 (4.3), fatalities 3-6 (4.1). All were treated with sedation, paralysis, hyperventilation (arterial carbon dioxide tension 3.0-3.5 kPa), intracranial pressure monitoring and moderate body surface hypothermia to 32 degrees C. Nine children died and 30 survived (nine intact, 13 minor disability, and eight major disability). The worst cerebral perfusion pressure was over 40 mm Hg in all but one survivor, and less than 40 mm Hg in seven of nine fatalities. Severe hypocapnia both in the first 24 hours and overall was correlated with poor outcomes (dead or major disability), as were bilateral contusions or diffuse axonal injury.